The Impact of Chronic Health Conditions on Length of Stay and Mortality in a General PICU*. Issue 1 (January 2017) - O'Brien, Scott; Nadel, Simon; Almossawi, Ofran; Inwald, David P.
Abstract : Objectives: Each year approximately 20, 000 children are admitted to PICUs across the United Kingdom. It is highlighted in several international studies that 40–70% of children admitted to PICUs have at least one chronic health condition that leads to increased length of stay and higher mortality rates. The prevalence of chronic health conditions in children admitted to U.K. PICUs is unknown. The purpose of this study was to use existing clinical data to explore the prevalence and impact of chronic health conditions on length of stay and mortality in a tertiary U.K. PICU. Design: Single-centre retrospective observational cohort study. Setting: Single, tertiary referral PICU. Patients: One thousand one hundred ninety-seven children 0–18 years old admitted between March 1, 2009, and February 28, 2013. Interventions: None. Measurements and Main Results: Data were derived from the unit's data submitted to the Paediatric Intensive Care Audit Network, the U.K. national PICU dataset. Data included demographics, diagnosis, Pediatric Index of Mortality-2 score, PICU interventions, PICU outcomes, chronic health condition etiologies, admission, and discharge dates and times. In total, 554 of 1, 197 (46.3%) had at least one chronic health condition. Of 554, 371 patients (67.1%) presented with a single chronic health condition, 126 (22.6%) with two chronic health conditions, and 57 (10.3%) with at least three chronic health conditions to a maximum of four chronic health conditions. There was a statistically significant difference in length of stay in those with a chronic health condition compared with those without (medians, 4 vs 3 d [interquartile range, 1–7 d]; Mann-Whitney U test, p < 0.001). The length of stay also increased significantly according to the number of chronic health conditions (Kruskal-Wallis test, p < 0.001). Mortality was significantly different between those with and without chronic health conditions (8.8% vs 5.4%; chi-square test, p = 0.024). Having two or at least three chronic health conditions significantly increased mortality compared with no chronic health conditions (odds ratio, 2.3 [CI, 1.2–4.55]; p = 0.013 and 2.95 [CI, 1.28–6.8]; p = 0.011), respectively. Conclusions: The increasing number of chronic healthcare conditions is associated with length of stay and mortality.